2020
DOI: 10.1038/s41598-020-62601-y
|View full text |Cite
|
Sign up to set email alerts
|

Scaling Behavior of Quasi-One-Dimensional Vortex Avalanches in Superconducting Films

Abstract: Scaling behaviour of dynamically driven vortex avalanches in superconducting YBa2Cu3O 7−δ films deposited on tilted crystalline substrates has been observed using quantitative magneto-optical imaging. Two films with different tilt angles are characterized by the probability distributions of avalanche size in terms of the number of moving vortices. It is found in both samples that these distributions follow power-laws over up to three decades, and have exponents ranging between 1.0 and 1.4. The distributions al… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 46 publications
0
3
0
Order By: Relevance
“…Furthermore, this experience is considered in the book [7]. Another amazing example is the statistics of vortex avalanches (magnetic flux avalanches) in high-temperature superconductors [36]. All this suggests the idea of the applicability of the R´enyi distribution to a wide range of systems and phenomena.…”
Section: Generalization Of the Power-law Distributionmentioning
confidence: 99%
“…Furthermore, this experience is considered in the book [7]. Another amazing example is the statistics of vortex avalanches (magnetic flux avalanches) in high-temperature superconductors [36]. All this suggests the idea of the applicability of the R´enyi distribution to a wide range of systems and phenomena.…”
Section: Generalization Of the Power-law Distributionmentioning
confidence: 99%
“…Within inhomogeneous SC films patterned with arrays of antidots [ 25 , 26 , 28 ], blind holes [ 27 , 29 ] and insulating particles [ 30 ], it is found that inhomogeneities strongly modify the current carrying capacity and dramatically change the flux avalanche patterns. Quantitative MOI measurements of the vortex avalanches in SC films show that the probability distributions of avalanche sizes follow power laws and demonstrate finite-size scaling [ 31 , 32 ]. In a recently-developed hypervelocity MOI system with two branches of pulsed laser, it is found that optically triggered vortex avalanches are driven by magnetic pressure and showed SOC and chaotic dynamics different from that commonly found [ 33 ].…”
Section: Introductionmentioning
confidence: 99%
“…Avalanche flux dynamics in thin films, with penetration field depth greater than their thickness, attracts special attention because of several phenomena, recently discovered by means of magneto-optic, including dendritic flux patterns [ 18 , 19 , 20 , 21 , 22 , 23 , 24 ]. Such avalanches consist of sharp impulses of the magnetic flux rushing into the specimen.…”
Section: Introductionmentioning
confidence: 99%